2019
DOI: 10.1038/s41467-019-10732-w
|View full text |Cite
|
Sign up to set email alerts
|

A neurotoxin that specifically targets Anopheles mosquitoes

Abstract: Clostridial neurotoxins, including tetanus and botulinum neurotoxins, generally target vertebrates. We show here that this family of toxins has a much broader host spectrum, by identifying PMP1, a clostridial-like neurotoxin that selectively targets anopheline mosquitoes. Isolation of PMP1 from Paraclostridium bifermentans strains collected in anopheline endemic areas on two continents indicates it is widely distributed. The toxin likely evolved from an ancestral form that targets the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 42 publications
1
53
0
Order By: Relevance
“…The extremely high potency of clostridial neurotoxins is due to the unique combination of two factors: (a) the very rapid binding to neurons, whose integrity is essential for survival, and (b) their enzymatic activity highly specific for the three SNARE proteins, whose cleavage is sufficient to block neurotransmitter release with ensuing neuroparalysis [2,3]. This is evident for vertebrates, but it is also true for invertebrates-particularly for flying insects, as shown by the very recent discovery of a BoNT-like neurotoxin specific for Anopheles mosquitos [92].…”
Section: Discussionmentioning
confidence: 99%
“…The extremely high potency of clostridial neurotoxins is due to the unique combination of two factors: (a) the very rapid binding to neurons, whose integrity is essential for survival, and (b) their enzymatic activity highly specific for the three SNARE proteins, whose cleavage is sufficient to block neurotransmitter release with ensuing neuroparalysis [2,3]. This is evident for vertebrates, but it is also true for invertebrates-particularly for flying insects, as shown by the very recent discovery of a BoNT-like neurotoxin specific for Anopheles mosquitos [92].…”
Section: Discussionmentioning
confidence: 99%
“…Although the mode of action of OrfX proteins is unknown, recent work in Paraclostridium bifermentans subsp. malaysia showed that the co-expression of OrfX proteins may increase the oral toxicity of the mosquitocidal toxin PMP1 [23]. The relatively high degree of conservation among OrfX and P47 (Figure 3 and Tables S1-S5) as opposed to the diversity of associated toxins (in terms of size, structure, mode of action) suggests that the OrfX and P47 proteins indirectly assist in toxin production, release, or trafficking.…”
Section: Discussionmentioning
confidence: 99%
“…This subcomplex is involved in the formation of tripartite ABC toxin of P. luminescens which is a well-studied example of RHS-repeat containing polymorphic toxin targeting insect larvae [52,53]. Recent studies showed that BoNT-like proteins can exhibit insecticidal potential [23], therefore the presence of bna next to the genes putatively encoding anti-insect toxin components did not appear coincidental. Accordingly, we discuss below whether incorporation of BNA into an ABC toxin complex can be rationalized.…”
Section: Identification Of Bont/ntnh-like Protein In Bacillus Sp 2shmentioning
confidence: 99%
“…Recent studies of clinical isolates also revealed a new mosaic toxin known as BoNT/H or BoNT/FA, with an LC most similar to a subtype of BoNT/F (BoNT/F5) and an H C similar to BoNT/A1-H C [11][12][13]. Most recently, a few BoNT-like toxins have been reported and characterized, including BoNT/X in a Clostridium botulinum strain [14], BoNT/En in an Enterococcus faecium strain [15], and Paraclostridial Mosquitocidal Protein 1 (PMP1) in Paraclostridium bifermentans strains [16].…”
Section: Introductionmentioning
confidence: 99%